2022
DOI: 10.3390/su14020683
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Serious Games in Economic and Business Education: A Case of ERP Business Simulation

Abstract: Digitalisation nowadays impacts business environments significantly. Therefore, if higher education wants to educate students properly for a successful career path, the business and economics curriculum must be enriched with innovative teaching approaches covering actual topics, such as, for example, the implementation of the ERPsim business simulation, a representative of serious games. The ERPsim business simulation is based on SAP ERP, and is aimed at teaching ERP concepts. It covers different business proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
1
26
0
2
Order By: Relevance
“…Specific simulation games were used in different courses to improve the content knowledge of students. For example, the pre-postgame survey' results of a study by Beranič and Heričko [62] showed a positive impact on students' knowledge in the business process and ERP transactions and in the domain of technical knowledge for SAP ERP. Similarly, a quantitative study by Angolia and Pagliari [119] discussed an ERP simulation game to aid students' conceptual learning of ERP systems in a supply chain course.…”
Section: Learning Outcomes Of Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific simulation games were used in different courses to improve the content knowledge of students. For example, the pre-postgame survey' results of a study by Beranič and Heričko [62] showed a positive impact on students' knowledge in the business process and ERP transactions and in the domain of technical knowledge for SAP ERP. Similarly, a quantitative study by Angolia and Pagliari [119] discussed an ERP simulation game to aid students' conceptual learning of ERP systems in a supply chain course.…”
Section: Learning Outcomes Of Usingmentioning
confidence: 99%
“…They observed students' active participation and social interaction and reported an overall positive impact on interactive skills. Other reported that the interactive skills enhanced by playing BSGs are communication, persuasion, and conflict resolution (i) Positive effects were reported concerning students' engagement with the simulation activity [43,46,62,65,67,68,76,83] (ii) Increased motivation toward playing simulation [4,41,42,64,65,69,84] (iii) Higher satisfaction levels with the course content [4,42,47,65,84] (iv) Increased self-efficacy [39,50,64,66,68,76] (v) Increased self-awareness and confidence [38,39,68,91] To conclude, most of the selected papers reveal positive effects regarding the use of computer simulation games on learning outcomes. Figure 12 shows the most common learning outcomes of BSGs identified in the selected papers of this review.…”
Section: Skill Outcomes Of Using Bsgsmentioning
confidence: 99%
“…(e.g., [62]), different groups of students (e.g., economics, computer science, law, etc.) (e.g., [130,131]), differences by using the same e-learning platforms in different countries (e.g., [132,133]), gender of students (e.g., [134]), age, etc. Another limitation of the research is that, over time, the importance of the studied factors of the research model changes [34], so it would be sensible to conduct longitudinal research in the future.…”
Section: Limitations and Suggestions For Future Workmentioning
confidence: 99%
“…A docência do ensino superior traz consigo muitos desafios, sendo que um dos principais obstáculos enfrentados pelos profissionais atuantes nessa modalidade de ensino, é reter a atenção dos alunos em sala de aula diante de um conglomerado de informações e avanços tecnológicos tais como: big data 1 , internet das coisas 2 e outros (Fardo, 2013). Essa explosão tecnológica faz com que a atenção dos alunos em sala de aula se disperse, principalmente quando não recebem estímulos suficientes para se concentrarem nas aulas (Beranic & Hericko, 2022).…”
Section: Introductionunclassified
“…A gamificação é um método de ensino que utiliza jogos de forma dinâmica com o protagonismo dos envolvidos no processo de aprendizagem (Beranic & Hericko, 2022). Especificamente, sua implementação nos cursos de Administração e Contabilidade coloca os estudantes em um ambiente de negócios, para que utilizem seu potencial e sua capacidade crítica à resolução dos conflitos.…”
Section: Introductionunclassified